The Trophic Status of Bandar Kayangan Reservoir Lembah SariRumbai Pesisir Sub District Pekanbaru City Province Riau Based on Phytoplankton Abundance - Tri Wahyudi; Tengku Dahril; Asmika H. Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Trophic Status shows the level of water fertility that can be measured from nutrient, transparency and other biological activities that occur in a body of water. The study has been conducted December - January 2019.This study aims to determine the trophic status of the reservoir based on the type and phytoplankton abundance. There were 4 station, namely Station 1 in  Ambang river (station 1), and merbau river (station 2), station 3 in zone transition and station 4 in zone lacustrine. Samples were carried out 3 time with one weak interval. The quality of water parameters is temperature, transparency, depth, acidity (pH), dissolved oxygen, free of carbon dioxide (CO2), nitrate (NO3), fosfat (PO4). The type of phytoplankton found 4 classes namely  Bacillariophyceae (2 species), Chlorophyceae (9 species), Cyanophyceae (4 species) and Dynophyceae (1 species).   Phytoplankton abudance range 5147cells/ Liter – 6454 cells/Liter. Water quality parameters such as transparency range 57 – 60,2 cm, temperature range 31-32oC, pH 5, dissolved oxygen range 5,38 – 8,31 mg/L, free carbon dioxide range 0,208 -0,293 mg/L, nitrate range 0,075 – 0,096 mg/L. Based on  phytoplankton abundance , the waters of the Bandar Kayangan reservoir can be categorized oligotrophic. Keyword: Phytoplankton, Water Quality Parameters, Oligotrophic